PO125 Pr-fampridine improves walking speed and quality of life in ms. (1st December 2017) - Ewe, Renee; Louissaint, Hannah; Bull, Kate; Allen, Joanne; Farrell, Rachel
Abstract : Background: Prolonged release Fampridine improves walking speed and quality of life in people with multiple sclerosis (MS). Licensed by European Medicines Agency (2011) it is not reimbursed on the NHS. Objectives: To assess effect of PR-Fampridine on walking speed, quality of life and functional ability in a novel 'MS walking clinic'. Methodology: People with MS related walking impairment were reviewed in complex specialist clinic. Treatments included functional electrical stimulation (FES), anti-spasmodics, PR-fampridine, physiotherpy. Outcomes: Timed-25-Foot Walk (T25FW), Multiple Sclerosis Walking Scale (MSWS-12), EuroQol5 (EQ-5D-5L), VAS walking, functional goals. Data was collected at baseline, 2–3 weeks and 4 monthly therafter. Responders were defined by ≥20% increase T25FW in baseline velocity with concomitant MSWS-12 improvement. Results: 269 subjects included. Mean age 52.3 [34–73 years], 186 female and 83 male. Mean Expanded Disability Status Score (EDSS) 6.39 [6.0–7.0]. 117 were timed walk (TW) responders (43%) with 65.0% improvement compared with 10.8% in TWnon-responders (p<0.0001). MSWS-12 improved in responders (−18.1, p=0.023) not in non-responders (−10.6, ns). EQ-5D-5L showed greater improvement responders compared with non-responders (0.119 vs 0.026, p=0.032). Response was sustained for up to 3 years. Conclusion: PR-Fampridine improves walking speed, self-reported walking ability and quality of life in an open-label longitudinal study of MS patients.